Professional ethics: facts and possibilities - Teixeira, Adélia Maria Santos (Brazilian Journal of Behavioral and Cognitive Therapy, 1999)
The professional ethics questions in Psychology is discussed from a tentative behavioral analysis of some verbal statements about moral and ethics. The dissociations between the ethical "speaking" and "doing" and the involved complexity in the assimilation of social contingencies, rules or laws are outlined. Some situations circumscribed in the academic environment and to the several psychologist’s action fields are mentioned as susceptible to ethical questioning. The rights recognitions and attributions are pointed out as the base for the ethical behaviors development and for the overcoming of the dissociation between the ethical "speaking” and "doing".